Identifying Novel Inborn Errors of the Immune System : Primary Immunodeficiencies with Defective Class Switch and Autoimmunity - Salzer, Elisabeth (Springer Fachmedien Wiesbaden : Imprint: Springer, 2017)
In her study Elisabeth Salzer describes three novel monogenic diseases. For CD27 deficiency Elisabeth Salzer describes a large cohort of patients. Although all patients shared the same causative missense mutation, they displayed diverse clinical presentations. In another patient she was able to identify a mutation in PRKCD resulting in a primary immunodeficiency with severe Lupus-like autoimmunity. The patient exhibited increased mRNA levels of IL6. Therefore, treatment with Tocilizumab, a humanized anti-IL-6 receptor monoclonal antibody was suggested. In a family with a history of deaths due to inflammatory bowel disease she identified a missense mutation in IL21. She produced wild type and mutated IL-21 protein and demonstrated a loss of function phenotype. As IL-21 is in clinical trials, she proposed a potentially curative treatment option. These discoveries contributed to the understanding of the multifaceted regulatory mechanisms of the immune system and highlighted essential players in these complex signaling networks. Contents CD27 Deficiency-Description of a Large Patient Cohort PRKCD Deficiency with Lupus-Like Autoimmunity IL-21 Deficiency Results in Very Early-Onset Inflammatory Bowel Disease Target Groups Scientists and students in the field of pediatrics, immunology, gastroenterology, rheumatology and genetics Pediatricians About the Author Dr. Elisabeth Salzer works on the discovery and description of novel immunodeficiencies in children and adolescents at the CeMM Center for Molecular Medicine. .
Keywords: Medicine.; Human genetics.; Immunology.; Pediatrics.; elektronické knihy; electronic books